Home office in the era of COVID-19 Pandemic – Exploration of perception and experience of managers - Wang, Junsheng (2022)
The goal of this thesis is to assess the perception and experience of managers as they had home office during the COVID-19 Pandemic, to explore changes in productivity and identify their causes. In-depth interviews with business managers and owners in the Czech Republic and China were conducted to provide qualitative data for analysis. The finding provides highlights on influencing aspects of home office, this knowledge can provide organisations a good reference of what to beware of when teleworking, helping other managers in understanding telework and formulation of their strategies towards telework.